2016
DOI: 10.1038/srep29975
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of calpains ameliorates vascular restenosis through MMP2/TGF-β1 pathway

Abstract: Restenosis limits the efficacy of vascular percutaneous intervention, in which vascular smooth muscle cell (VSMC) proliferation and activation of inflammation are two primary causal factors. Calpains influence VSMC proliferation and collagen synthesis. However, the roles of calpastatin and calpains in vascular restenosis remain unclear. Here, restenosis was induced by ligating the left carotid artery, and VSMCs were pretreated with platelet-derived growth factor (PDGF)-BB. Adenovirus vector carrying MMP2 seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
1
14
0
1
Order By: Relevance
“…Previous studies reported roles for MMP2 in regulating lung cancer invasion and vascular permeability . In the present study, exogenous overexpression and interference experiments showed that lnc‐MMP2‐2 promoted lung cancer invasion and increased vascular permeability, and that lnc‐MMP2‐2 expression was markedly higher in lung cancer tissues than in normal controls.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies reported roles for MMP2 in regulating lung cancer invasion and vascular permeability . In the present study, exogenous overexpression and interference experiments showed that lnc‐MMP2‐2 promoted lung cancer invasion and increased vascular permeability, and that lnc‐MMP2‐2 expression was markedly higher in lung cancer tissues than in normal controls.…”
Section: Discussionsupporting
confidence: 60%
“…The main calpain isoforms in the brain are μ-calpain (calpain-1) and m-calpain (calpain-2) [ 24 ]. Some studies have indicated that, under certain conditions, calpain activation could cause tissue damage and cell death [ 25 , 26 ]. However, some studies showed that calpain-1 and calpain-2 play opposite roles in retinal ischemia/reperfusion injury but both, calpain-1 and calpain-2, provide neuroprotection in chronic myeloid leukemia [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, osteopontin and osteonectin levels in VSMCs were reduced by the overexpression of calpain-1 in rats, inducing the calcification and fibrosis in the arteries of aged rats ( 67 ). Furthermore, VSMC proliferation and collagen synthesis were accelerated during ligation-induced carotid restenosis in mice, which was opposed by the transgenic overexpression of calpastatin ( 68 ). Therefore, calpain systems have a pivotal role in inflammation-related fibrogenic responses in VSMCs.…”
Section: Contribution Of Defective Protein Catabolism To Atherogenic mentioning
confidence: 99%